2021
DOI: 10.3390/diagnostics11020352
|View full text |Cite
|
Sign up to set email alerts
|

Paravertebral Muscle Mechanical Properties and Spinal Range of Motion in Patients with Acute Neck or Low Back Pain: A Case-Control Study

Abstract: Our aims were to identify potential differences in muscle mechanical properties (MMPs) of cervical and lumbar tissues and in spinal range of motion (ROM) between patients with acute low back pain (LBP) or acute neck pain (NP) and healthy controls, and to identify if ROMs and MMPs are able to identify subjects among the three groups. Clinical variables (pain, disability, fear of movement, kinesiophobia, quality of life), MMPs and ROMs were obtained in 33 subjects with acute LBP, 33 with acute NP, and 33 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 83 publications
8
24
1
Order By: Relevance
“…Our results are in line with previous studies that showed higher lumbar myofascial stiffness as a physical sign in AS patients [ 6 ] or in axSpA patients [ 15 , 32 ]. In fact, the current results showed higher tone, stiffness and decrement (linear elastic properties), and lower relaxation and creep (viscoelastic properties) for the axSpA patients than those reported for young asymptomatic subjects [ 14 ] and for acute spinal pain patients [ 15 ]. Therefore, axSpA increases lumbar and cervical muscle tone, which keeps increasing as the disease progresses [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are in line with previous studies that showed higher lumbar myofascial stiffness as a physical sign in AS patients [ 6 ] or in axSpA patients [ 15 , 32 ]. In fact, the current results showed higher tone, stiffness and decrement (linear elastic properties), and lower relaxation and creep (viscoelastic properties) for the axSpA patients than those reported for young asymptomatic subjects [ 14 ] and for acute spinal pain patients [ 15 ]. Therefore, axSpA increases lumbar and cervical muscle tone, which keeps increasing as the disease progresses [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…For cervical muscles, it was identified that there is a consistent relationship between age, decrement and stiffness in healthy women [ 37 ], and also in mechanical cervical and lumbar pain [ 15 ] in our data of axSpA patients. This relationship was stronger than the relationship between decrement and stiffness with BMI and head posture.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations